Total Edge Irregularity Strength of the Disjoint Union of Helm Graphs - Muhammad Kamran Siddiqui; N. Nurdin; Edy Tri Baskoro (Institute for Research and Community Services (LPPM) ITB, 2013)
The total edge irregular k-labeling of a graph G=(V,E) is the labeling of vertices and edges of G in such a way that for any different edges their weights are distinct. The total edge irregularity strength, tes (G), is defined as the minimum k for which G has a total edge irregular k-labeling. In this paper, we consider the total edge irregularity strength of the disjoint union of m special types of helm graphs.